Identification of inappropriate prescribing in a Brazilian nursing home using STOPP/START screening tools and the Beers' Criteria - Mariana Martins Gonzaga Nascimento; Andréia Queiroz Ribeiro; Mariana Linhares Pereira; Adriana Cristina Soares; Antônio Ignácio de Loyola Filho; Carlos Alan Candido Dias-Junior (Universidade de São Paulo, 2014)
The objective of this study was to determine the prevalence of Potentially Inappropriate Medication (PIM) use and associated factors, as well as the prevalence of Prescribing Omissions (PO). A cross-sectional study was conducted in a philanthropic Brazilian nursing home involving 46 individuals aged 60 years or older. The following information was collected from medical records and drug prescriptions: gender, age, health conditions and drugs used in the past thirty days. PIM and PO were identified according to the Beers' Criteria and the STOPP/START screening tools. Over one third (37%) of the population used at least one PIM according to the Beers' Criteria (n=17) and 60.9% according to the STOPP tool. A significant association was found between polypharmacy (use of five or more drugs) and use of PIM according to the Beers' Criteria, but not according to the STOPP. Eight residents (17.4%) were exposed to eight PO. This study allowed the diagnosis of a concerning drug utilization profile with use of a high number of PIMs. Thus, there is an evident need to implement strategies for improving geriatric prescription.